MAGNETIC RESONANCE QUANTIFICATION OF MENISCUS VASCULARITY IN PEDIATRIC VERSUS ADULT KNEES. Issue 4 (28th April 2020) - Lin, Kenneth M.; Gadinsky, Naomi E.; Klinger, Craig E.; Dyke, Jonathan P.; Rodeo, Scott A.; Green, Daniel W.; Fabricant, Peter D.; Helfet, David L.; Shea, Kevin G.; Lazaro, Lionel E.
Background: Despite advances in surgical techniques, implant technology, and biological augmentation, one innate limitation to meniscus healing is lack of vascularity. Ability to quantify meniscal vascularity has been limited with previous techniques, and minimal data exists describing differential vascular zones in the skeletally immature meniscus. Purpose/Hypothesis: The objective of this study is to use quantitative contrast-enhanced magnetic resonance imaging (MRI) to compare meniscal vascularity in pediatric cadaveric specimens to adults. We hypothesize that the developing meniscus has greater and more uniform vascularity throughout all zones. Methods: We utilized 10 fresh-frozen human cadaveric knees (5 immature knees, age 0-6 months; 5 mature knees, age 34-67 years). Gadolinium-enhanced MRI was performed using a previously established vascularity quantification protocol. Regions of interest corresponding to peripheral and central zones of the meniscus were identified on pre-contrast coronal images, and signal enhancement (normalized against background tissue) was compared between pre-and post-contrast images (Figure 1). Results: Quantitative MRI demonstrated increased perfusion in the peripheral zones compared to the central zones (2.3:1 in immature knees and 3:1 in mature knees) in the medial and lateral menisci separately, and both menisci aggregated. Overall, the medial and lateral menisci had similar levels of perfusion in all specimens (45.9% ± 8.3% medial vs. 54.1% ± 8.3% lateral in immature knees; 50.5% ± 11.3% medial vs. 49.5% ± 11.3% lateral in mature knees). Immature specimens demonstrated greater overall normalized meniscal signal uptake, with the 0-month specimen demonstrating the greatest proportional signal enhancement. Conclusion: While blood flow to peripheral zones is greater than to central zones in both immature and adult menisci, younger menisci receive proportionally greater overall blood flow compared to adults, including greater blood flow to the inner zone, challenging the conventional wisdom of the central zone being avascular. As younger patients become increasingly active in sports, thorough understanding of the immature meniscus is required. Greater overall vascularity, including centrally, to the developing meniscus suggests improved healing potential following injury, and further encourages meniscal preservation when possible. : Figure 1. Analysis of meniscal vascularity using contract-enhanced magnetic resonance imaging. A:Schematic drawing of peripheral and central zones of the medial and lateral menisci used for quantification.B:Mid-coronal images showing pre-and post contract images with ROIs delineated in adult and pediatric specimens; there is significatly increased perfusion to the epiphysis in the immature knee. Figure 2. Quantification of mensical vascularity in each specimen Comparsion of relative vascularity of peripheral versus central zones shows significantly greater blood flow to outer zone across all specimens.Quantification of total vascular contribution from the medial and lateral menisci aggregated showed a trend towards greater proportional blood flow in younger specimens.